The effect of rhizosphere on growth of Sphingomonas chlorophenolica ATCC 39723 during pentachlorophenol (PCP) biodegradation in batch culture and soil - Rosemeri Inês Dams; Graeme Paton; Ken Killhan (Biotemas)
Studies on the influence of the rhizosphere on the growth of Sphingo- monas chlorophenolica during. Pentacholophenol (PCP) degradation in batch culture and in soil were carried out. In batch culture, a basal minimal medium with or without rhizosphere exudates extracted from winter wheat was used. In soil systems, degradation experiments were performed in the presence and absence of plants. Measurements of PCP concentrations were made using high performance liquid chroma- tography analysis (HPLC). Bacterial analyses of S. chlorophenolica were carried out by plating on MSM medium. The results showed that the rhizosphere exudates stimulated the growth of the cells of S. chlorophe- nolica at concentrations of 50 and 80mg kg dry wt soil –1 as well as stimu- lating the ability of S. chlorophenolica to degrade PCP at a concentration of 80mg Kg dry wt soil -1. In addition, pentachlorophenol had an adverse effect on the growth of S. chlorophenolica. The introduction of S. chlorop- henolica into the loamy soil with plants showed a faster degradation when compared to the inocu- lated soil without plants. There was a significant increase of S. chloroph- enolica in the roots in comparison to those in thesoil. This study showed that the presence of the inoculum S. chlorophe nolica enhanced the PCP degradation in a loamy soil and it indicates the potential for a treatment process under a appropriate environmental conditions such as there present in soil systems.